IDENTIFIKASI RUMPUT LAUT (Seaweed) DI PERAIRAN PANTAI CEMARA KABUPATEN LOMBOK TIMUR SEBAGAI DASAR PENYUSUNAN BROSUR BAGI MASYARAKAT - Muhammad Sopiandi Hamdan Kasim; Baiq Muli Harisanti; Ali Imran (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
This study was aimed to determine the identification of macroalgae species in Cemara Beach, Jerowaru District, East Lombok Regency, as the basis for developing biodiversity brochure for public. This is a descriptive explorative research with sampling technique devided into 4 transects: 1) transect I was in the litoral zone with water conditions that were still quite natural because of lack of influence from the residents; 2) transect II was located in litoral zone near the residential area; 3) transect III was placed in the neritic zone with relatively natural area; and 4) while the transect IV is placed which have same zone as the transect III, but difference by the aquatic environment was directly affected by human activities around the coast. Identification of macroalgae was carried out by in-situ method. Community structure of macroalgae were analyzed using the Shanon-Wiener formula. Based on the results there were found 15 species of macroalgae belonging to the three main divisions namely: Rhodophyta (Red Algae); Phaeophyta (Brown Algae); and Chlorophyta (Green Algae). Based on the results of the validation (graphics, materials, and grammar) by the validator team, concluded that the seaweed diversity brochure was very well qualified without revised so that it was categorized very good for dissemination to public.